Knowledge structure maps based on Multiple Domain Matrices. (2013) - C., M.; Schenkl, Schenkl; A., S.; Schmidt, Schmidt; M., D.; Hense, Hense; J., J.; Mandl, Mandl; H., H.; Maurer, Maurer; M, M
No abstract available